EFFECTS OF MATERNAL SMOKING ON PLACENTAL MORPHOLOGY - Ashfaq, Muhammad; Janjua, Muhammad Zahoor; Nawaz, Muhammad (Journal of Ayub Medical College Abbottabad, 2003)
Back ground: Maternal smoking is one of leading causes of premature labour and low birth weight babies. Nicotine and carbon monoxide both induce degenerative changes as well as premature aging of placenta. Degenerative changes induce increased amount of collagen in chorionic villi and increased thickness of subtrophoblastic basement membrane. Premature aging is indicated by increased number of syncytial buds and higher percentage of apoptosis in smoker's placentae. Premature aging and degenerative changes may reduce the functional component of placenta and lead to abnormal outcome of pregnancy. This study was designed to determine the effects of maternal smoking on placental morphology. Methods: Total 40 full term placentae, 20 from normal and 20 from smoker mothers were studied histologically. Full thickness pieces of each placenta from standard area were taken for paraffin embedment. Four micron thick sections were cut on rotary microtome and stained with haematoxylin and Eosin, Malloryis trichrome and hexamine silver for syncytial buds, Apoptotic cells, chorionic villous collagen and Subtrophoblastic basement membrane. Results:This study demonstrates that there is extensive aging and degenerative changes in smoker's placentae. The aging process is shown by increased syncytial buds per unit area and high percentage of apoptosis. Degenerative changes are indicated by increased amount of collagen in chorionic villi and increased thickness of subtrophoblastic basement membrane. Conclusion: Extensive premature aging and degenerative changes in smoker's placentae decrease the functional component of an organ, reducing its nutritive and excretory functions. This may be the cause of low birth weight babies in smokers. Extensive loss of trophoblasts by apoptosis and syncytial buds may lead to hormonal imbalance and premature labour in smokers. Keywords: Placenta, Smoking, Degeneration, Aging